2021
DOI: 10.1038/s41419-021-03546-6
|View full text |Cite
|
Sign up to set email alerts
|

AAV2-mediated and hypoxia response element-directed expression of bFGF in neural stem cells showed therapeutic effects on spinal cord injury in rats

Abstract: Neural stem cell (NSCs) transplantation has been one of the hot topics in the repair of spinal cord injury (SCI). Fibroblast growth factor (FGF) is considered a promising nerve injury therapy after SCI. However, owing to a hostile hypoxia condition in SCI, there remains a challenging issue in implementing these tactics to repair SCI. In this report, we used adeno-associated virus 2 (AAV2), a prototype AAV used in clinical trials for human neuron disorders, basic FGF (bFGF) gene under the regulation of hypoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Focusing on the paralysis of lower limbs after spinal cord injury, we combined swimming with a treadmill to allow rats to perform active rehabilitation training through the synergistic effect of water flow and the conveyor belt. The current experimental results show that the motor function of rats was significantly improved after treadmill training for 14 d. In addition, GAP43 and NF200 were used to evaluate neuronal and axonal injury [ 27 29 ]. As expected, we found that the expression of GAP43 and NF200 significantly decreased due to neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the paralysis of lower limbs after spinal cord injury, we combined swimming with a treadmill to allow rats to perform active rehabilitation training through the synergistic effect of water flow and the conveyor belt. The current experimental results show that the motor function of rats was significantly improved after treadmill training for 14 d. In addition, GAP43 and NF200 were used to evaluate neuronal and axonal injury [ 27 29 ]. As expected, we found that the expression of GAP43 and NF200 significantly decreased due to neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The results of MRI tests proved the migration of transplanted cells toward the injury site of the spinal cord that could functionally connect to host neurons and substantially enhance locomotor functions while expressing neural lineage markers. These results imply that the transplantation of these cells could regulate inflammatory cells and glia activation and improve the hyperalgesia that occurred after SCI [45]. Moreover, the combination transplantation of NSCs and human olfactory ensheathing mucosa cells has shown effectiveness in preclinical trials to treat post-traumatic cysts of spinal cord injuries.…”
Section: Neural Stem Cells (Nscs)mentioning
confidence: 88%
“…According to a mechanistic study, this therapy could increase the expression of basic FGF and enhance total functional recovery compared to the control group (AAV2-5HRE-NSCs) by increasing the expression of specific neuronal proteins and reducing the expression of the glial fibrillary acidic protein and autophagy-associated proteins (Figure 2). Overall, AAV2-5HRE-bFGF-NSCs treatment could upgrade the recovery of SCI in rats by enhancing successful nerve regeneration as well as inhibiting cell autophagy and glial scar formation [45].…”
Section: Neural Stem Cells (Nscs)mentioning
confidence: 98%
“…Together, these findings have important implications for potential therapeutic strategies for CNS diseases. 147 At present, NSC transplantation is a hot topic in the treatment of stroke, 148 spinal cord injury, 149 traumatic brain injury, 150 and other CNS diseases. Indeed, NSCs were shown to induce the release of Mir‐133b in BMSCs to promote the survival of neurons, thus further improving the therapeutic effect of NSC transplantation on cardiac arrest‐induced brain injury.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%